2009
DOI: 10.1530/rep-09-0208
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone and interferon tau-regulated genes in the ovine uterine endometrium: identification of periostin as a potential mediator of conceptus elongation

Abstract: During early pregnancy in ruminants, progesterone (P 4 ) and interferon tau (IFNT) act on the endometrium to regulate genes hypothesized to be important for conceptus development and implantation. The present study was conducted to verify several candidate genes (actin a-2, smooth muscle, aorta (ACTA2), collagen, type III, a-1 (COL3A1), periostin (POSTN), secreted protein acidic cysteine-rich (SPARC), S100 calcium-binding protein A2 (S100A2), STAT5A and transgelin (TAGLN)) regulated by pregnancy, P 4 , and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
0
20
1
Order By: Relevance
“…There is much evidence to suggest that SPP1 mRNA expression is regulated by progesterone and does not appear to be influenced by IFNT in the ovine endometrium (see review by Johnson et al 2003). Progesterone control was not indicated in the present study and a recent report suggested that SPP1 was regulated independently of pregnancy, IFNT and progesterone in an ovine cell culture system (Ahn et al 2009). Levels of SPP1 mRNA in NP uteri were lower compared with in the endometrium from SR and IR pregnancies with large conceptuses, but this could be attributed to other conceptus factors, such as CSH1, as mentioned previously.…”
Section: Evaluation Of the Bovine Uterine Environmentcontrasting
confidence: 50%
“…There is much evidence to suggest that SPP1 mRNA expression is regulated by progesterone and does not appear to be influenced by IFNT in the ovine endometrium (see review by Johnson et al 2003). Progesterone control was not indicated in the present study and a recent report suggested that SPP1 was regulated independently of pregnancy, IFNT and progesterone in an ovine cell culture system (Ahn et al 2009). Levels of SPP1 mRNA in NP uteri were lower compared with in the endometrium from SR and IR pregnancies with large conceptuses, but this could be attributed to other conceptus factors, such as CSH1, as mentioned previously.…”
Section: Evaluation Of the Bovine Uterine Environmentcontrasting
confidence: 50%
“…Hiroi et al (60) suggested that POSTN might mediate estrogen-action via integrin both activating Akt/PKB and FAK-mediated pathways in the endometrium. Studies on animal models (60,61) showed that POSTN was mainly hyper-expressed in the early secretory stage, the same phase in which there was an increase of integrin α v β 3 and α v β 5 expression too. In this specific phase, POSTN may induce endometrial decidualization, trophoblastic cells migration and invasion through the activation of integrins and the Akt/PKB pathway (60,62).…”
Section: Human Embryo Implantation Shares Many Biological Characterismentioning
confidence: 99%
“…Because these FGFs preside in the uterus during peri-implantation development in cattle and sheep, we set out to determine whether FGF2 and FGF10 regulate trophoblast cell migratory activity by examining how these factors impact oTr1 cell migration in vitro. This cell line was developed from an elongating ovine conceptus (day 15 of gestation; Farmer et al 2008) and is used extensively to examine various aspects of trophoblast activity, including cell migration (Hayashi et al 2007, Ahn et al 2009, Simmons et al 2009). Studies were completed using a previously described assay examining the movement of oTr1 cells through Corning Transwell inserts containing 8 mm pores .…”
Section: Fgf2 and Fgf10 Stimulate Migration Of Ovine Trophoblast Cellsmentioning
confidence: 99%
“…Several uterine-and conceptus-derived factors induce trophoblast cell migration. These include epidermal growth factor (EGF), insulin-like growth factor 2 (IGF2), galectin-15 (SGAL15), WNT5A, and periostin (POSTN; Hayashi et al 2007, Ahn et al 2009, Simmons et al 2009. Several signaling molecules have been linked with this activity, and several of the aforementioned factors utilize MAP kinases (MAPKs), phosphoinositide 3-kinase (PI3K), Rho-kinase, or a combination of these pathways to control migration rates (Hayashi et al 2007.…”
Section: Introductionmentioning
confidence: 99%